An outbreak of thyroid hyperplasia (goiter) with high mortality in budgerigars (Melopsittacus undulatus). (January 2015) - Loukopoulos, Panayiotis; Bautista, Adrienne C.; Puschner, Birgit; Murphy, Brian; Crossley, Beate M.; Holser, Ian; Gomes, Lucy; Shivaprasad, H. L.; Uzal, Francisco A.
An outbreak of goiter with high morbidity and mortality in a flock of budgerigars ( Melopsittacus undulatus ) in California is described. Forty-five out of 400 adult birds exhibited signs of illness, weight loss, and enlargement in the crop area; 15 of the 45 birds died over a 2–3-month period. Diet consisted of a commercial mixture with the addition of broccoli, whole oats, and carrots, but no minerals or supplements. Six budgerigars were subjected to necropsy; all 6 birds had severely enlarged thyroid glands. Thyroid follicular hyperplasia was histologically observed in all birds examined, while granulomatous thyroiditis and microfollicular adenoma were observed in 2 birds, respectively. Virological, bacteriological, parasitological, and heavy metal analyses were negative or within normal limits. The total iodine in the thyroid glands of affected birds was measured by inductively coupled plasma–mass spectrometry. Following iodine supplementation and removal of broccoli from the diet, the owner reported weight gain and a reduced death rate among clinically affected birds; no additional birds became sick. The presence of broccoli with its iodine-binding ability and the complete lack of added minerals in the diet of these animals were thought to be the predisposing factors for the outbreak in the present study. Outbreaks of goiter accompanied by high mortality are rare in any species and, to the best of the authors' knowledge, have not been described previously in any avian species. Recognition of this condition may help improve medical, welfare, and trade standards concerning this species.